2013
DOI: 10.1186/1475-2875-12-455
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lymphocytes in patients with Plasmodium vivax malaria and its relation to the annexin-A1 and IL-10

Abstract: BackgroundMalaria is the most prevalent parasitic disease in the world. In Brazil, the largest number of malaria cases (98%) is within the Legal Amazon region, where Plasmodium vivax is responsible for over 80% of diagnosed cases. The aim of this study was to investigate the annexin-A1 expression in CD4+, CD8+ T cells, regulatory T cells (Treg) and cytokine IL-10 quantification in plasma from patients with malaria caused by P. vivax.MethodsThe quantification of the cytokine IL-10 of patients infected with P. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…In the present study, vivax malaria patients have shown significant low RANTES/CCL5 levels, but just weakly associated with IL-6, IL-12p40, IFN-γ or MCP-1/CCL2. The lower levels of RANTES/CCL5 could be explained by the CD8 + T cells reduction [4345] and thrombocytopaenia [8, 10, 11, 4446] observed during vivax malaria. A study carried out with children infected with P. falciparum observed an association between thrombocytopaenia and lower RANTES plasma levels [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, vivax malaria patients have shown significant low RANTES/CCL5 levels, but just weakly associated with IL-6, IL-12p40, IFN-γ or MCP-1/CCL2. The lower levels of RANTES/CCL5 could be explained by the CD8 + T cells reduction [4345] and thrombocytopaenia [8, 10, 11, 4446] observed during vivax malaria. A study carried out with children infected with P. falciparum observed an association between thrombocytopaenia and lower RANTES plasma levels [47].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that there is a reduction in the percentage and/or absolute number of CD8 + T cells in the peripheral blood during acute P. falciparum or P. vivax infection [ 10 - 14 ], and these reductions have been attributed to the apoptosis of these cells [ 15 , 16 ], the reallocation of T cells to sites of inflammation [ 12 , 17 ] or other factors such as the suppression of CD8 + T cells induced by sporozoites or infected red blood cells [ 18 ]. In regard to P. vivax infection, however, reports have shown that there is no significant difference in the percentage of CD8 + T cells during an acute malaria infection compared with that in uninfected individuals [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in patients infected with Plasmodium vivax, AnxA1 expression was increased in regulatory T cells and decreased in CD4 + and CD8 + T cells. Additionally, it has been suggested that AnxA1 may contribute to IL-10 production in plasma of patients with vivax malaria (45). Considering the increase in AnxA1 serum levels in ML patients, our findings suggest that upregulation of AnxA1, similarly to other anti-inflammatory markers (68), is not effective to counterbalance the higher levels of proinflammatory mediators present in ML patients, including higher levels of TNF-a.…”
Section: Discussionmentioning
confidence: 63%
“…AnxA1 expression has been extensively investigated in models of sterile inflammation, leading to the recognition of its role as a key modulator of both of the innate and adaptive immune systems (15,43). However, in the context of intracellular parasite infection only few studies (28,44,45) have been reported, including the demonstration that AnxA1 expression is locally increased in LCL lesions caused by L. braziliensis infection (29). Given that L. braziliensis infection may lead patients to develop an exacerbated inflammatory response, with intense tissue damage in chronic disease stages (3,4,6), the understanding of the mechanisms involved in the modulation of inflammatory responses, including AnxA1 expression, in leishmaniasis may provide new insights for the development of effective therapies.…”
Section: Discussionmentioning
confidence: 99%